2023
DOI: 10.5599/admet.1622
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, current status and emerging strategies in the development of rapidly dissolving FDM 3D-printed tablets: An overview and commentary

Abstract: Since the approval of a 3D-printed tablet by the FDA in 2015 for marketing, there has been a great interest in 3D printing in the pharmaceutical field for the development of personalized and on-demand medications. Among various 3D printing methods explored for the development of oral solid dosage form like tablet, the fused deposition modeling (FDM) 3D-printing, where the drug-polymer mixtures are first converted into filaments by hot melt extrusion (HME) and then the filaments are printed into tablets using 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…On the other hand, an increased API content modifies the crystallographic, thermal and rheological properties of the filament, with the possibility of rendering them unprintable [116]. Since FDM is a mechanical process, failure within moving parts can affect the printing process [117]. Crucially, there is only a handful of suitable thermoplastic polymers suited for use in FDM 3DP pharmaceutical dosage forms [72].…”
Section: Challengesmentioning
confidence: 99%
“…On the other hand, an increased API content modifies the crystallographic, thermal and rheological properties of the filament, with the possibility of rendering them unprintable [116]. Since FDM is a mechanical process, failure within moving parts can affect the printing process [117]. Crucially, there is only a handful of suitable thermoplastic polymers suited for use in FDM 3DP pharmaceutical dosage forms [72].…”
Section: Challengesmentioning
confidence: 99%
“…The main method for preparing drug-loaded filaments for use in typical FDM 3D printers is hot melt extrusion (HME) technology. In the HME process, active pharmaceutical ingredients (APIs) are blended with thermoplastic polymers, melted below their glass transition temperature, and subsequently extruded by screws in the HME [ 13 , 14 ]. There are several challenges faced during the preparation of drug-loaded filaments for HME and commercial 3D printing; for example, the original filaments, available for commercial 3D printing, are mainly composed of acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial products of solid dispersion prepared by hot-melt extrusion can comprise various polymeric carriers [8]. Polyvinylpyrrolidone, copovidone, and cellulosic polymers are widely used in commercially and in research [8][9][10][11][12]. Studies on polymeric carriers revealed that hydroxypropyl methylcellulose acetate succinate (HPMCAS) has better physical stability and oral absorption than other carriers [13][14][15] and is used in a commercial product, "Noxafil  ".…”
Section: Introductionmentioning
confidence: 99%